Stress concentration factors in concrete-filled square hollow section joints with perfobond ribs. (15th February 2019) - Jiang, Lei; Liu, Yongjian; Fam, Amir
Highlights: Stress Concentration Factors (SCFs) are established for novel truss chord-brace welded joints. Chord is a concrete-filled square hollow section stiffened with Perfobond Leister (PBL) ribs. Joints with varying dimensions were first tested to measure hot spot stresses. 3D FE models were developed and verified then used in comprehensive parametric study. Design equations for SCF were developed based on multiple regression analysis of database. Abstract: A novel tubular joint of concrete-filled square hollow section (CFSHS) chord welded to an SHS brace was studied experimentally and numerically to establish design equations for Stress Concentration Factors (SCFs) for fatigue design purposes. The chord was stiffened with internal perfobond ribs longitudinally welded to the inner faces. A series of joints with varying member sizes and wall thicknesses were first tested under axial force in the brace and the hot spot stresses were carefully measured. Three-dimensional finite element models were developed and validated with the experimental results. A comprehensive parametric study was then conducted on 90° T- and X-joints with perfobond ribs, to establish correlations between SCF and three key non-dimensional geometric parameters: brace width-to-chord width ( β ), width-to-wall thickness ratio of the chord (2 γ ), and brace wall thickness-to-chord wall thickness ratio ( τ ). Four basic loading conditions were examined: axial tension and in-plane bending in the brace, and axial tension and in-plane bending in the chord. Finally, a series of SCF formulae and design charts were proposed based on multiple regression analysis. It was shown that under brace axial tension stress concentrations reduced by one third and two thirds in CFSHS chords without perfobond ribs and with perfobond ribs, respectively, compared to a SHS chord. Current design guides which are based on SHS sections, overestimate SCFs significantly for CFSHS sections with perfobond ribs.